2021
DOI: 10.1155/2021/5604642
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Research on Surrounding Rock Unloading during Solid Coal Roadway Excavation

Abstract: In order to further explore the deformation and failure essence of the deep coal body, based on the characteristics of surrounding rock stress adjustment before and after solid coal roadway excavation, an experiment of unloading confining pressure and loading axial pressure of the coal body was designed and conducted in this study. Based on test results, the failure mechanics and energy characteristics of the coal body were analyzed through experiments. Rapid unloading is considered a key factor contributing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Yi et al 22 analyzed the laws of strain energy transfer and dissipation in deep roadways surrounding rock when considering the objective strain softening and dilatancy behavior, then analyzed the large deformation mechanism of surrounding rock. Guo et al 23 analyzed the failure mechanics and energy characteristics of coal mass on the basis of confining pressure unloading and axial pressure loading experiments, and showed that rapid unloading was the key factor leading to lateral deformation and expansion failure of coal mass. Zhang et al [24][25][26] based on the operating vibration signal acquisition system, studied the basic characteristics of microseismic events in the heading face, including the occurrence location, main frequency range, maximum amplitude range, event duration, and the relationship between stress and deformation in the heading face.…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al 22 analyzed the laws of strain energy transfer and dissipation in deep roadways surrounding rock when considering the objective strain softening and dilatancy behavior, then analyzed the large deformation mechanism of surrounding rock. Guo et al 23 analyzed the failure mechanics and energy characteristics of coal mass on the basis of confining pressure unloading and axial pressure loading experiments, and showed that rapid unloading was the key factor leading to lateral deformation and expansion failure of coal mass. Zhang et al [24][25][26] based on the operating vibration signal acquisition system, studied the basic characteristics of microseismic events in the heading face, including the occurrence location, main frequency range, maximum amplitude range, event duration, and the relationship between stress and deformation in the heading face.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant mechanical properties of engineering coal and rock mass serve as the foundation for the design, construction, and related disaster prevention of geotechnical and underground engineering and have always been favored by the scientific and technological workers all the time. In recent years, some studies have shown that in practical engineering, especially underground or mining engineering, the stress characteristics of excavation surrounding rock are more in line with the stress path of unloading confining pressure and axial loading [3][4][5]. Zhao [6] analyzed the rock mechanic principle of major deep engineering in details and discussed eight unsolved century-old problems of rock mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Some in depth research revealed that the mechanical parameters of the rock mass under loading and unloading conditions were significantly different [3]. In addition, the actual excavation process included in deep engineering projects (such as the roadway excavation [4]) shares more similarities with the unloading path [5]. Compared to the loading path, the measured mechanical parameters of the unloading path tend to be more accurate [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al [22,23] utilized cement mortar to process roadway surrounding rock specimens, and conducted a series of excavation and unloading model tests. Some studies also indicated that the stress adjustment process of surrounding rock in roadway excavation can be simplified as the stress path of unloading confining pressure [4,5], indicating that the initial stress, unloading confining pressure rate, and loading axial pressure speed, etc., can directly affect the damage and destruction of surrounding rock. However, few relevant studies have been conducted on the mechanical tests of coal and rock mass under the aforementioned stress path conditions, its energy evolution, and practical guidance, in combination with actual engineering.…”
Section: Introductionmentioning
confidence: 99%